Higiene oral de niños, adolescentes y jóvenes con discapacidad cognitiva leve - Córdoba Urbano, Doris Lucia; Portilla Cabrera, María Isabel; Arteaga Caiza, Guillermo Alirio (Universidad y Salud, 2010)
Objective: To determine the level of Oral Hygiene (OH) of children, teenagers and younger adults with mild cognitive impairment related to age, gender, social status and health scheme. Method: A descriptive, cross-sectional with non-probability sampling and convenience was carried out. 109 people with mild cognitive impairment between 6-25 years attending the Educational Center PROFESA were examined. OH was assessed through the Bacterial Plaque Index of Silness and Löe (BPISL). Measures of central tendency and Kruskal-Wallis test for statistical analysis were used. Results: General BPISL is 1.83 which represents intermediate and regular OH. Men and women are at a medium level of bacterial plaque presence, 64.5% of men and 74.4% of women have average levels of OH. The highest BPISL was found between the ages 10-14 and 15-19. Conclusion: People with cognitive disabilities have mid-level BPISL, mainly teenagers. The responsibility for the OH conditions depend on parents, caregivers and educators, in addition to dental professionals who should get involved in the process of establishing good habits in this population.